Salvia luteistriata (Lamiaceae), a new species from northeastern Sichuan, China - Hu, Guo-Xiong; Liu, En-De; Zhang, Ting; Cai, Jie; Xiang, Chun-Lei (Phytotaxa, 2017)
Salvia luteistriata, a new species from northeastern Sichuan, China, is described and illustrated here. The new species morphologically resembles S. maximowicziana, but it can be easily distinguished from the latter by having bigger maroon corolla with showy creamy-yellow vertical stripes in the internal ventral surface of corolla tube. Other diagnostic characters between them include that the new species has bigger leaf blade, longer bract and pedicel, bigger oblong upper corolla lip, and bigger mericarp. An identification key for the species in Salvia ser. Maximowiczianae, including S. luteistriata, is provided.